UPAYA PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN MELALUI MEDIA PERPUSTAKAAN HURUF ABJAD PADA KELOMPOK A RA AS SYAFI’IYAH PONOROGO - Anugrah Dewi Nurmawati; Ida Yeni Rahmawati; Betty Yulia Wulansari (EDUPEDIA, 2020)
This research aims to: (1) describe and explain the process of improving children's early reading skills through the letters of the alphabet library media, (2) describing and explaining the results of improving initial reading skills achieved by children through letter library media.This type of research is a collaborative classroom action research. Subjects were 27 group A children consisting of girls and boys. The object of research is early reading skills. This research consisted of two cycles and each cycle consisted of three meetings. Data collection techniques in this research are observation and documentation. The data analysis technique was carried out in a qualitative and quantitative description.The result of this research show that early reading skill of children there are  steps by step in the learning process through the alphabetical media library are: 1) Classes are formed with the format "U” 2) Showing learning props in the form of a library of letters. 3) Explain how to use as well as demonstrate. 4) After understanding, children take turns demonstrating. 5) After demonstrating correctly the child is asked to pronounce the letters listed on the letter library media. 6) The teacher gives praise to children who are able to speak (pronounce letters) with the help of the media library of letters. 7) The teacher provides motivation to children who are still unable to speak (pronounce letters) with the media library of letters. The result of this research show that early reading skill of child in grade A of RA As Syafi’iyah Ponorogo is already increase like the successfully criteria while choose earlier. The result in the pre-action activities 7.4% increased in the first cycle to 14.8%, and increased during the second cycle to 81.4%.Keywords: Reading Skills, Alphabet Letter Library, Early Childhood